2013
DOI: 10.1345/aph.1r620
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Migraine in Adults: A Review of Pharmacotherapeutic Options

Abstract: Abdominal migraine should be considered a possible source of incurable abdominal pain in adults when accompanied by a complete gastrointestinal workup with normal results. We recommend a trial of topiramate as prophylactic therapy if abdominal migraine is the likely source of the pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…In support of this possibility, there is a marked co-morbidity of migraine with other pain syndromes, including irritable bowel syndrome and fibromyalgia syndrome and temporomandibular disorder (van Hemert et al, 2014; Vij et al, 2015). Furthermore, there are migrant variants that affect other body regions, such as abdominal migraine (Woodruff et al, 2013), which has been suggested to be responsive to triptans in some patients (Russell et al, 2002). It is possible that dural nociceptors have unique properties for migraine-related changes in the neurovascular unit in the dura; a systematic evaluation of whether administration of GTN enhances pain in other body domains in humans is required to address this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this possibility, there is a marked co-morbidity of migraine with other pain syndromes, including irritable bowel syndrome and fibromyalgia syndrome and temporomandibular disorder (van Hemert et al, 2014; Vij et al, 2015). Furthermore, there are migrant variants that affect other body regions, such as abdominal migraine (Woodruff et al, 2013), which has been suggested to be responsive to triptans in some patients (Russell et al, 2002). It is possible that dural nociceptors have unique properties for migraine-related changes in the neurovascular unit in the dura; a systematic evaluation of whether administration of GTN enhances pain in other body domains in humans is required to address this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The acute attacks are generally responsive to NSAIDs, especially when associated with antiemetics, whereas a minority of patients respond to abortive sumatriptan therapy. Although a number of treatments have been proposed [22], including prophylactic migraine therapies (ie, calcium-channel blockers, β-blockers, topiramate, and antihistamines), the therapeutic strategy remains elusive.…”
mentioning
confidence: 99%
“…Children with AMs usually grow out of the condition but some may grow up to experience migraine headaches and recurrent abdominal pain as adults 3 . The diagnostic criteria for AM have been established in children, 4,5 and our review of the literature shows evidence of AM being diagnosed in adults 6‐17 . Here, we present the case of a 58‐year‐old female who met the established diagnostic criteria for AM following three hospital readmissions and extensive workup to rule out other etiologies.…”
Section: Introductionmentioning
confidence: 94%
“…Given the absence of clear migraine headaches in this patient or in her family history, the decision was made treat her emesis‐dominant AM symptoms with a trial of prochlorperazine as opposed to a triptan. While not first line, prochlorperazine has been shown to have antiemetic properties including in an AM patient 8,18,19 . This gave her sustained relief from her symptoms, and she was able to tolerate a regular diet and discharged.…”
Section: Abdominal Migraine Diagnosis and Treatmentmentioning
confidence: 99%